2016
DOI: 10.1002/ecs2.1574
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impacts of the decline of Tsuga canadensis stands on two amphibian species in a New England forest

Abstract: Citation: Siddig, A. A. H., A. M. Ellison, and B. G. Mathewson. 2016. Assessing the impacts of the decline of Tsuga canadensis stands on two amphibian species in a New England forest. Ecosphere 7(11):e01574. 10.1002/ecs2.1574Abstract. Disturbances such as outbreaks of herbivorous insects and pathogens can devastate unique habitats and directly reduce biodiversity. The foundation tree species Tsuga canadensis (eastern hemlock) is declining due to infestation by the nonnative insect Adelges tsugae (hemlock wooll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…These conclusions are timely and consistent with many recent studies in the region [36][37][38] that found a declining trend in abundance of red-backs in New England forests. Moreover, although the coverage of this study is relatively small, it confirmed our expectations regarding the contribution of invasive pests and habitat disturbances to the wide scale decline of amphibian populations.…”
Section: Discussionsupporting
confidence: 91%
“…These conclusions are timely and consistent with many recent studies in the region [36][37][38] that found a declining trend in abundance of red-backs in New England forests. Moreover, although the coverage of this study is relatively small, it confirmed our expectations regarding the contribution of invasive pests and habitat disturbances to the wide scale decline of amphibian populations.…”
Section: Discussionsupporting
confidence: 91%
“…, Siddig et al. ). Based on our comparisons of soil organic layer mass and %C content between hemlock forest and mature birch stands, we estimate a 6.8× difference in the C pool held in the forest floor (477.4 g C/m 2 vs. 70.6 g C/m 2 ), which suggests the potential for a ~4.5 ton C release per hectare if hemlock organic layers decomposed and transitioned to a new, lower equilibrium comparable to nearby mature birch stands.…”
Section: Discussionmentioning
confidence: 99%
“…, Siddig et al. ). In addition to their influence on ecological communities and other species, foundation tree species like hemlock affect ecosystem processes such as decomposition, nutrient cycling, and carbon sequestration (Ellison et al.…”
Section: Introductionmentioning
confidence: 99%
“…We focus on two species of amphibians common in such New England hemlock forests: red-backed salamanders (Plethodon cinerus; hereafter "red backs") and eastern red-spotted newts (Notopthalmus viridescens viridescens; hereafter "red efts"). Both species are highly abundant in the region, and their abundances have been found to decline with the loss of hemlock forest, demonstrating their potential sensitivity to changes in such systems [11,40,41]. Data are drawn from an ongoing experiment at the Harvard Forest Long-Term Ecological Research Site (HFR); some additional comparisons are made with studies of salamanders in two other forested LTER sites, the Hubbard Brook Experimental Forest (HBR) and the Coweeta Experimental Forest (CWT).…”
Section: Introductionmentioning
confidence: 99%